1993
DOI: 10.1093/carcin/14.11.2219
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by dietary curcumin of azoxymethane-induced ornithine decarboxylase, tyrosine protein kinase, arachidonic acid metabolism and aberrant crypt foci formation in the rat colon

Abstract: The present study was designed to investigate the modulatory role of dietary curcumin on (i) azoxymethane (AOM)-induced ornithine decarboxylase (ODC), tyrosine protein kinase (TPK) and arachidonic acid metabolism in liver and colonic mucosa of male F344 rats, (ii) in vitro arachidonic acid metabolism in the liver and colonic mucosa and (iii) AOM-induced aberrant crypt foci (ACF) formation in the colon of F344 rats. At 5 weeks of age groups of animals were fed one of the experimental diets containing 0 or 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
1
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(105 citation statements)
references
References 0 publications
2
100
1
1
Order By: Relevance
“…[14][15][16][17] Curcumin's chemopreventive effectiveness has also been documented during the promotion/progression phases of colon carcinogenesis. 25,26 One of the important mechanisms of prevention of carcinogenesis by curcumin is downregulation of several cytochrome p-450 enzymes and induction of phase II metabolizing enzymes such as glutathione S-transferase translating into decreased M 1 G DNA adduct formations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] Curcumin's chemopreventive effectiveness has also been documented during the promotion/progression phases of colon carcinogenesis. 25,26 One of the important mechanisms of prevention of carcinogenesis by curcumin is downregulation of several cytochrome p-450 enzymes and induction of phase II metabolizing enzymes such as glutathione S-transferase translating into decreased M 1 G DNA adduct formations.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Curcumin has also been shown to prevent the development of adenomas in the intestinal tract of Min1/2 mice, a model of human familial adenomatous polyposis. 19 In a Phase I clinical trial, curcumin has been found to be effective in inhibiting the growth of a variety of tumors.…”
mentioning
confidence: 99%
“…IP address: 13.66.222.141, on 20 Apr 2019 at 01:12:24, subject to the Cambridge Core terms of use, available absolute requirement for the proliferation of a variety of human tumour cells both in vitro and in vivo (Luk, 1992), and inhibitors of ODC have been shown to deplete polyamine levels and block proliferation in cultured cells (Mamont et al 1976) and in tumours in vivo (Pegg, 1988). It has been proposed that the ability of the flavonoid apigenin to suppress skin tumorigenesis in mice, and of curcumin, a constituent of turmeric, to suppress early markers of tumorigenesis in the rat colon, may be related to reduced ODC levels in the target tissues (Wei et al 1990;Rao et al 1993). Other flavonoids that have been reported to inhibit promoter induced increases in ODC include kaempferol, luteolin, morin and fisetin (Nakadate et al 1984;Fujiki et al 1986).…”
Section: Polyamine Metabolismmentioning
confidence: 99%
“…However, it has been shown to be only a very weak direct inhibitor of cyclo-oxygenase enzyme activity (Srivastava and Srimal, 1985). It also has chemopreventive activity in animal models of colon cancer (Rao et al, 1993;Pereira et al, 1996), but its mechanism of action is not well understood. It has been shown to inhibit COX2 expression (Kelley et al, 1996), and in separate studies to be a potent inhibitor of NF-kB activation (Sanjaya and Aggarwal, 1995;Bierhaus et al, 1997;Kumar et al, 1998), but not of its binding to DNA (Bierhaus et al, 1997).…”
Section: Introductionmentioning
confidence: 99%